PENGARUH THIN CAPITALIZATION TERHADAP PENGHINDARAN PAJAK PERUSAHAAN INDEX SAHAM SYARIAH INDONESIA - Ayu Andawiyah; Ahmad Subeki; Arista Hakiki (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2019)
The purpose of this study was to examine the effect of thin capitalization with to cash effective tax rates as the proxy for tax avoidance. Control Variable used in this research is key management compensation, firms size, and profitability. The method used in this research is an analytical descriptive. The sample used in this research consist of 20 companies from manufacturing sector listed in Indonesian Stock Shariah Index (ISSI) in 2011– 2016. Sample selection methods used in this research is purposive sampling. The analysis methods used in this research is multiple regression analysis. The results show that the thin capitalization has a significant influence on cash effective tax rates as the proxy for tax avoidance. Key management compensation as control variable has not been able to prove the effect on tax avoidance and firms size profitability have a significant effect on cash effective tax rates as the proxy for tax avoidance.